Optical coherence tomography for observation of the olfactory epithelium in mice. Issue 2 (April 2019) - Ueda, Toshio; Sakamoto, Tatsunori; Kobayashi, Masayoshi; Kuwata, Fumihiko; Ishikawa, Masaaki; Omori, Koichi; Nakagawa, Takayuki
Abstract: Objective: Optical coherence tomography (OCT) is an imaging tool that exploits the coherence of infrared light and is clinically utilized in the field of ophthalmology and dermatology. This study aimed to examine the feasibility of using OCT for diagnosing degeneration and regeneration of the olfactory epithelium in mice. Methods: The olfactory and respiratory epithelia in excised nasal septa of adult mice were observed using OCT. Subsequently, histological assessments were performed with hematoxylin and eosin (H–E) staining. The thicknesses of the olfactory or respiratory epithelia were measured in both OCT images and H–E-stained paraffin sections. The ability of OCT to distinguish olfactory epithelia from respiratory epithelia in normal mice was compared with that of H–E staining. The feasibility of using OCT assessments for detecting changes in the thickness of olfactory epithelia was tested in a mouse model of the degeneration and regeneration of olfactory epithelia. Results: OCT allowed visualization of the gross morphology of the olfactory and respiratory epithelium in normal mice, although it was limited in terms of visualizing cellular components. OCT-based measurements of epithelial thickness helped to distinguish olfactory epithelia from respiratory epithelia. Similar to H–E staining, OCT also clarified changes in the olfactory epithelium thickness after methimazole application. Conclusions: These findings indicate the utility of OCT for assessment of olfactory epithelial thickness and its potential for clinical evaluation of human olfactory epithelia.